Analisis Laporan Keuangan Dalam Mengukur Tingkat Profitabilitas Pada Perusahaan Sistem Penyediaan Air Minum dan Sanitasi (SPAMS) Appakabaji Kabupaten Maros - Putri Meylani Haruna; Renny Mointi; Aminah Aminah (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to analyze the company's financial ratios so that companies can find out, whether the company's ratio value can meet industry standards or vice versa. The object of this research is the Appakabaji Water Supply and Sanitation System (SPAMS) company in Salenrang Village, Bontoa District, Maros Regency, using secondary data, namely data obtained in ready-to-use form. With quantitative methods. Using profitability ratio analysis tools in the form of, gross profit margin, net profit margin, return on assetss and return on equity. The results of the study found that the company experienced fluctuations or experienced unstable financial performance. In calculating the profitability ratio, it can be said that financial performance is in poor condition, so that the results of the analysis, are below the industry standards that have been set.